2021
DOI: 10.1111/evj.13488
|View full text |Cite
|
Sign up to set email alerts
|

Gross post‐mortem and histological features in 27 horses with confirmed lumbosacral region pain and five control horses: A descriptive cadaveric study

Abstract: Background: There is a lack of understanding of the pathological and/or physiological nature of lumbosacral region pain.Objectives: To describe the gross variations of the osseous and soft tissues of the lumbosacral region and report the histological findings of sections of nerve tissue in affected and control horses. Study design:Descriptive post-mortem case series.Methods: All horses had undergone full clinical and gait assessment, including ridden exercise. Horses with a substantial response to infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…15,16 However, a recent post-mortem study of horses with a positive response to periarticular injection of mepivacaine reported both sacroiliac joint and lumbosacral pathology. 17 In addition, there were gross abnormalities of the sciatic and obturator nerves, not observed in control horses, and higher histological scores in the lumbosacral plexus and the cranial gluteal nerve, sciatic and obturator nerves compared with control horses. These results indicate the potential extent of diffusion of local anaesthetic solution.…”
Section: Diffusion Of Local Anaesthetic Solution To Nerve Roots and A...mentioning
confidence: 79%
“…15,16 However, a recent post-mortem study of horses with a positive response to periarticular injection of mepivacaine reported both sacroiliac joint and lumbosacral pathology. 17 In addition, there were gross abnormalities of the sciatic and obturator nerves, not observed in control horses, and higher histological scores in the lumbosacral plexus and the cranial gluteal nerve, sciatic and obturator nerves compared with control horses. These results indicate the potential extent of diffusion of local anaesthetic solution.…”
Section: Diffusion Of Local Anaesthetic Solution To Nerve Roots and A...mentioning
confidence: 79%
“…9,10 In addition, some anatomic variations of the lumbosacral segment may alter the normal biomechanics of the area, predisposing to an early development of abnormal changes or inability to work correctly, resulting in poor performance. 11 While there are some necropsy studies 12,13 of the thoracolumbar region of the vertebral column in horses, only a few have focused on the lumbosacroiliac region and are mostly based on Thoroughbred racehorse specimens. [3][4][5]14 The aim of the study reported here was to describe the incidence of anatomic variations and abnormal changes of the lumbosacroiliac region in a mixed population of horses (ie, variable breeds, ages, and size).…”
Section: Objectivementioning
confidence: 99%
“…In total, 38 specimens were included in this study, similar to previous anatomic studies in this field. 3,5,11,14 The breeds consisted of warmblood (n = 13), Thoroughbred (4), Anglo-Arabian (4), Arab (3), Standardbred (3), and others (11). There were 25 females and 13 males, ranging in age between 5 and 30 years (mean, 16 years; SD, 6.5 years) and weighing between 284 and 620 kg (mean, 489 kg; SD, 65 kg).…”
Section: Specimensmentioning
confidence: 99%
“…In recent years there has been considerable global research effort to improve understanding of the functional biomechanics of the sacroiliac joint and related pelvic musculature, [3][4][5][6] and to document the pathological conditions that may contribute to pain and dysfunction through diagnostic imaging [7][8][9] and post mortem studies. 10,11 The pitfalls of over diagnosis by skeletal scintigraphy have been highlighted. 7,12 In his letter, Mr Gray stated that 'The February article displays a misunderstanding of the significance of the sacroiliac joint in equine lameness; the prevalence of which has been exaggerated; and the part it plays in lameness has never been proven'.…”
mentioning
confidence: 99%
“…7,15,16 We strongly believe in the value of diagnostic anaesthesia of the sacroiliac joint region in horses showing suggestive clinical signs, acknowledging that, just like many other local anaesthetic techniques, it is not entirely specific. 7,9,11,15 Nonetheless, it greatly helps to localise the source of pain causing a gait abnormality and/or poor performance. Others may feel averse to diagnostic anaesthesia, mostly because of experience of or perceived risk of complications and make their diagnosis based on response to medication and/or diagnostic imaging.…”
mentioning
confidence: 99%